DEVELOPMENT OF STS MARKERS BASED ON AFLP FRAGMENTS LINKED TO THE ROOT TRAITS FOR BREEDING DROUGHT RESISTANCE RICE LINES - Liên, Nguyễn Thị Kim (Vietnam Journal of Biotechnology, 2011)
MAS is the mordem breeding used commonly nowaday. MAS based on estimating exactly sites of genes on the map and the tightly relationships between the markers and the interested genes to estimate genotype of individuals in population. Molecular markers such as RAPD, AFLP, RFLP have been used for mapping but they cannot be directly used in breeding. These markers, they must be developped to STS markers so that they can be used for MAS. To apply MAS need a lots of easy and typical STS markers linked to genes confrolling interested fraits. Following the results on the QTLs mapping by AFLP markers for some root fraits related to drought resistance, we have developped STS markers from AFLP fragments for the use in MAS. We have cloned and sequenced six AFLP fragments linked to root number, root thickness, root length, root weight to shoot ratio and deep root weight to shoot ratio. From these sequences we designed six pairs of STS primers. We found out the PCR conditions for STSAVM62, STSAVM22, STSAVM87 primers with respective annealing temperature 54*’C, 53°C and 60*’C. However, the PCR products were not polymorphic. To create the polymorphism between lines, we attemped to use a single STS primer. As the results when amplified forward primer of STSAVM62, the polymorphic band of lOOObp was obtained. This band, proved to be stable in the population and inherited through progenies so it can be used in breeding of drought resistance rice lines.